2009
DOI: 10.1007/s10514-009-9148-5
|View full text |Cite
|
Sign up to set email alerts
|

EL-E: an assistive mobile manipulator that autonomously fetches objects from flat surfaces

Abstract: Assistive mobile robots that autonomously manipulate objects within everyday settings have the potential to improve the lives of the elderly, injured, and disabled. Within this paper, we present the most recent version of the assistive mobile manipulator EL-E with a focus on the subsystem that enables the robot to retrieve objects from and deliver objects to flat surfaces. Once provided with a 3D location via brief illumination with a laser pointer, the robot autonomously approaches the location and then eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(85 citation statements)
references
References 45 publications
0
85
0
Order By: Relevance
“…A potential way to improve the proposed model relies on additional depth features. In the literature, several depth features have been proposed and investigated, such as surface curvature, depth gradient and orientation contrast [32] [58] [59]. However, since it has been demonstrated that the influence of these features might largely differ from one another [41], the application of more depth features raises the demand for a potential normalization step for each feature dimension and a more sophisticated pooling strategy.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…A potential way to improve the proposed model relies on additional depth features. In the literature, several depth features have been proposed and investigated, such as surface curvature, depth gradient and orientation contrast [32] [58] [59]. However, since it has been demonstrated that the influence of these features might largely differ from one another [41], the application of more depth features raises the demand for a potential normalization step for each feature dimension and a more sophisticated pooling strategy.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…121.015 And in 2010, performance measurements, although not for industrial use, were performed by Advait and Kemp [21] to evaluate completion of specific tasks for a mobile manipulator. The robot approached and grasped objects from 25 object categories that were ranked most important for robotic retrieval by motor-impaired patients.…”
Section: Mobile Manipulator Performance Measurementmentioning
confidence: 99%
“…S3C2410 board in the system in the hardware part, and is also the core of the hardware part, through the S3C2410 port of the USB board connected to the camera, receiving video information collected from the camera, the video information will be collected through the cable to send [2] [3].…”
Section: Design Main Modulementioning
confidence: 99%